Clays and Clay Minerals, Vol. 59, No. 3, 277–285, 2011. - Stojakovic, Djordje; Milenkovic, Jelena; Daneu, Nina; Rajic, Nevenka (My University, 2009)
Toxic metal contamination of waste waters can be mitigated by metal adsorption to clay and zeolitic minerals, but in developing countries such environmental remediation can be cost prohibitive if these minerals are not readily available. Because of its abundance, low cost, and excellent selectivity for several toxic metal ions, clinoptilolite from the Zlatokop deposit in Serbia was investigated for its ability to remove copper ions from aqueous solutions and serve as an effective local resource for this purpose. The sorption capacity of the clinoptilolite at 298 K varied from 8.3 mg Cu g-1 (for C0 = 100 mg Cu dm-3) to 16.8 mg Cu g-1 (for C0 = 400 mg Cu dm-3). The sorption data were best described by the Freundlich isotherm and the sorption kinetics followed the pseudo-second-order model. Intra-particle diffusion of Cu2+ was present but it is not the rate-limiting step. The sorption of Cu2+ on the clinoptilolite occurred spontaneously, the free energy change decreasing with temperature. The sorption was endothermic and was accompanied by an increase in entropy. Dehydration of the Cu-loaded clinoptilolite at 540ºC led to the formation of nanocrystalline Cu(I) oxide particles with an average size of ~2 nm, suggesting possible novel applications for the Cu-loaded clinoptilolite.
A Study Of The Removal Of Copper Ions From Aqueous Solution using Clinoptilolite From Serbia
05-sto.pdf- 372KB
Keywords: Periodicals; Geology; Clinoptilolite; Copper Removal; Kinetics; Nano-cuprite; Thermodynamics